Effectiveness of gamification in teaching and learning mathematics - Ariffin, Noor Amalina Nisa; Ramli, Nazirah; Nik Badrul Alam, Nik Muhammad Farhan Hakim; Yusof, Yusharina; Suparlan, Azimah (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2022)
Recent years have seen the development of a new culture in the teaching and learning process, such as the implementation of gamification. The application of gamification aims to enhance the teaching and learning process as well as the experience and satisfaction of those who participated. Recently, much ongoing research have been focusing on improving the quality of the teaching and learning process. The implementation of gamification activities in teaching and learning shows its ability to increase participants' experiences, responses, and engagements to the educational sessions. Therefore, increasing numbers of research are performed to explore the suitable types and approaches of gamification that can be used in education. On the other hand, while improving the quality of the education's environment is a key factor, it is also important to explore the satisfaction and motivation of all learners in this new adaptation to the education environment. The objective of this paper is to investigate the factors influencing students' scores via the implementation of the gamification elements in their Mathematics classes. Their expectations, experiences, motivations, as well as satisfaction in Mathematics classes were analysed via multiple linear regression analysis to study the learners' perspective towards the implementation of gamification in education. The results show a significant relationship between all factors with the student's assessment score. The increment in students' motivation to study and participate in class activities contribute to their performance in the subject taught. The regression model showing the relationship between students' motivation in class and their final assessment marks has been presented. The present result might contribute to the better teaching and learning environment option. Our youngsters nowadays need a new treatment in teaching and learning delivery. Hence, it is highly recommended to implement gamification activities in teaching and learning lessons. This study validates that gamification is also effective in Higher Education to promote better learning in challenging subjects.